First-Time Fathers’ Experience of Support from Midwives in Maternity Clinics: An Interview Study - L. Huusko; S. Sjöberg; A. Ekström; E. Hertfelt Wahn; S. Thorstensson (Nursing Research and Practice)
Background. Research shows that first-time fathers want to take part in preparation for birth and parenthood but they describe being excluded by health professionals. Aim. The aim of this study was to illustrate first-time fathers’ experiences of support from midwives in maternity clinics as a step in the validation of “The Father Perceived-Professional-Support” (The FaPPS) scale. Methods. A qualitative content analysis with an inductive and deductive approach was used; seven first-time fathers were strategically selected and interviewed. In the inductive part the following open question was asked: “How did you perceive the support from the antenatal midwife/midwives?” In the deductive part, the fathers were asked to respond to the FaPPS scale, in order to receive their thoughts and understanding of the scale, inspired by the “Think-aloud” method. Findings. The inductive results showed two main categories: Experience of not knowing what support they needed and Experience of being excluded. The fathers found support from other fathers in parental education classes, but they lack time to discuss. Overall it seems as if the fathers answered both from their own perspective and from the mothers’ perspective. This was not evident in the deductive results. The FaPPs scale should therefore include professionals’ ability to strengthen social support from other first-time fathers and professionals’ ability to offer support to the mother. Conclusion and Clinical Implications. The fathers experienced exclusion both by themselves and also by midwives. Midwives should offer both parents the opportunity to pose questions. It is important for expectant fathers that time for discussion is planned in parental education classes. The FaPPS scale is useful but needs further development. Parts of our result are in line with earlier research, for decades; therefore it is necessary to focus more on support for fathers.